The Language Teacher Profile Grid as an Instrument for Evaluating Teaching Competencies in Spanish as a Second Language in Costa Rica - Amador Solano, María Gabriela (2026)
The 21st century demands an improved professional profile for educators, which entails assessing the level of development oftheir competencies. The main objective of this article is to evaluate the proficiency levels of teachers of Spanish as a SecondLanguage (SSL) currently working in Costa Rica, with the aim of identifying their training needs. The methodology used was qualitative, consistent with educational research, as the study was conducted within the context of teacher training. The participantsconsist of two types of informants, selected through stratified sampling: teachers and curricular program coordinators. From among all Costa Rican institutions that teach Spanish as a second language, a sample of 20 institutions and 60 participants was selected.One of the data collection instruments was the Language Teacher Profile Grid, which outlines six stages of developmentwithin a tripartite framework: novice, independent, and expert. By using a graphic representation of the stages of professional development of the participants, key teaching competencies that need to be strengthened have been identified, namely: administrative management, assessment, and digital competence.